Anthropogenic land-use change decreases pollination and male and female fitness in terrestrial flowering plants - Aguilar, Ramiro; Cristóbal-Pérez, E Jacob; Marquez, Victoria; Carbone, Lucas M; Paglia, Isis; Freitas, Leandro; Ashworth, Lorena; Martén-Rodríguez, Silvana; Wilson Fernandes, Geraldo; Lobo, Jorge; Fuchs, Eric J; Quesada, Mauricio (Annals of botany, 2025)
The majority of the Earth's land area is currently occupied by humans. Measuring how terrestrial plants reproduce in these pervasive environments is essential for understanding their long-term viability and their ability to adapt to changing environments. We conducted hierarchical and phylogenetically independent meta-analyses to assess the overall effects of anthropogenic land-use changes on pollination, and male and female fitness in terrestrial plants. We found negative global effects of land-use change (i.e. mainly habitat loss and fragmentation) on pollination and on female and male fitness of terrestrial flowering plants. Negative effects were stronger in plants with self-incompatibility systems and in plants pollinated by invertebrates, regardless of life form and sexual expression. Pollination and female fitness of pollination-generalist and pollination-specialist plants were similarly negatively affected by land-use change, whereas male fitness of specialist plants showed no effects. Our findings indicate that angiosperm populations remaining in fragmented habitats negatively affect pollination, and female and male fitness, which will probably decrease the recruitment, survival and long-term viability of plant populations remaining in fragmented landscapes. We underline the main current gaps of knowledge for future research agendas and call not only for a decrease in the current rates of land-use changes across the world but also to embark on active restoration efforts to increase the area and connectivity of remaining natural habitats.